Psikologi Pendidikan Islam Sebagai Solusi Untuk Mengatasi Stres Akademik Mahasiswa PAI Universitas Negeri Padang (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Academic stress is one of the significant challenges faced by students, especially students of the Islamic Religious Education (PAI) Study Program at Padang State University (UNP). Previous studies show that many students experience severe pressure due to workload, academic demands, and difficulty balancing religious and academic activities. However, approaches based on Islamic values, such as those offered by Islamic Educational Psychology, have not been widely explored as a comprehensive solution to overcome this stress. This research aims to analyze how Islamic Educational Psychology can be an effective approach in managing PAI students academic stress. This research uses a qualitative approach with a case study method. The research participants consisted of 5 PAI students who experienced academic stress, as well as lecturers in Islamic religion courses at the Faculty of Social Sciences, UNP. Data was collected through in-depth interviews, observation and document analysis. The data analysis technique was carried out thematically, emphasizing patterns of findings that are relevant to the role of Islamic values ​​in stress management. The research results show that the integration of Islamic values, such as patience, trust, gratitude, as well as worship practices such as evening prayers and dhikr, helps students manage academic stress. Students who apply the concept of Islamic Educational Psychology tend to have better mental resilience and see academic pressure as a process of self-maturation. Apart from that, support from the campus environment, such as spiritual guidance and motivation based on Islamic values ​​from lecturers, plays a significant role in helping students overcome academic pressure. The conclusion of this research confirms that Islamic Educational Psychology is an effective approach in improving students' mental well-being, so it needs to be strengthened in the education system.
Keywords: Psychology; Islamic Education; Stres; Mental Health